Diseño estructural de una Finca Agroecoturística ubicada en la Parroquia Lloa, Cantón Quito, provincia de Pichincha - Vaca Maldonado, Katherine Lucero (2017)
This research project was established due to the need to generate sustainable and innovative tourist alternatives; Through the study, information was gathered that could change the lifestyle and the concept of tourism that society has in the future, all based on sustainable agricultural and tourist practices with environmental responsibility, and with this, adequate alternatives were established in around the development of tourism and the generation of green jobs. The research subjects a structural design of an agro-ecotourism farm in the Lloa parish, Quito canton of the Pichincha province, using agroecotourism as a means of alternative tourism that allows taking advantage of the existing resources in the area without neglecting the primary activities of the sector, this being the activity agricultural. To carry out this research, it is necessary to know the current state of the study area, which was developed through a situational diagnosis with a SWOT analysis, a strategic matrix and the use of a summary table to know what the tourism potential of the sector is and at the same time the collection of accurate and timely information that will serve as the baseline of the study by which the main problems can be detected and how they can be solved is allowed. A market study is also necessary to determine the percentage of demand and supply. In addition, a survey was carried out that allowed defining the services and products based on the needs of the users. Finally, the engineering of the project was established with its requirements which gave way to the structural design of the farm with its activities and characteristics defined in terms of agroecotourism. For a consumerist and immediatist society, new tourism products must be developed that satisfy the needs of users, this alternative tourism modality is a great option that can change the concept of tourism in the country and achieve that long-awaited balance between nature and man.